Impact of Neem (Azadirachta indica) leaf extract on the management of whitefly in the tomato crop - Abu Bakr Alzahaf (AlQalam Journal of Medical and Applied Sciences, 2026)
The study was conducted in the Higher Institute of Agricultural Techniques, Derna, Al-Fattayah, in the city of Derna, Libya. A positive impact of the treatment is evident. There are distinct morphological differences between the treatments, with the treated plants achieving the highest mean values for the number of inflorescences per lateral, the number of branches per plant, and fruit weight. The results showed that the number of branches in the treated plants averaged 7, compared to 6 branches in the control group. Regarding the number of inflorescences, the treated plants recorded an average of 14 inflorescences per branch, while the control group averaged 11 inflorescences per branch. Statistical analysis comparing the means reveals that the average fruit weight of the treated plants was 135.95 g, compared to 116.40 g for the control. Additionally, another difference was noted in the lateral growth of the canopy; the treated plants recorded an average width of 103.68 cm, while the control plants recorded an average width of 85.16 cm.